Rahmatan Lil 'Alamin Exegesis as Post-Conflict Inter-Religious Resolution in Poso, Indonesia (1998-2001) - Abdul Basid; Nor Surilawana Sulaiman (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
The inter-religious conflict in Poso, Indonesia, has had a substantial impact on the harmony of the region's multicultural society. This research aims to examine the potential of the Rahmatan Lil 'Alamin Verse Resolution in resolving the conflict by raising two main questions: (1) how Indonesian society responds to the inter-religious conflict in Poso, and (2) how the Rahmatan Lil 'Alamin Verse Resolution can be applied to resolve the inter-religious conflict in Poso. This research collected data through in-depth interviews, participatory observation, and documentation studies using a qualitative approach with a descriptive-analytical design. Research participants included religious leaders, local communities, local government, and relevant academics. Data were analysed thematically to identify emerging patterns and themes. The result of the research is that applying the Rahmatan Lil 'Alamin principle, which boils down to compassion, justice and tolerance, can be a strategic basis for building peace in Poso. The interpretation of various scholars shows that this mercy is inclusive and universal, covering all levels of society. Implementing this concept through multicultural education, interfaith dialogue, and traditional mechanisms such as Dalihan na Tolu has proven effective in easing tensions and preventing conflict escalation